KONTRIBUSI PENDAPATAN PEKERJA USAHA BERKAH CONE TERHADAP PENDAPATAN KELUARGA DI KELURAHAN SUMOMPO KECAMATAN TUMINTING KOTA MANADO - Elfira , Sari; Gene Henfried Meyer Kapantow; Audrey Julia Maria Maweikere (Sam Ratulangi University, 2021)
This study aimed to determine the contribution of income of the Berkah Cone business workers to their family income. This research was conducted for 3 months, starting from January to March 2020. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with Berkah Cone business workers and Berkah Cone business owners. Secondary data were obtained from monographs of Sumompo Sub-district and literature related to research. The sampling method used was a census to all workers consisted of 12 people. The results of this study indicated that the income of the Berkah Cone business workers has a 69.75% contribution to the family income. The value of 69.75% according to the contribution assessment criteria belongs to the very large category (> 50%). This means that the income earned by workers in the Blessing Cone business greatly helped their families and themselves in fulfilling theirdaily needs and making a real contribution to the family income.